Practical CGM : a guide to improving outcomes through continuous glucose monitoring - Scheiner, Gary (American Diabetes Association, 2015)
Use of real-time continuous glucose monitors among people with type 1 and type 2 diabetes is growing rapidly and should continue to grow until an artificial pancreas is brought to market. Likewise, use of professional systems in healthcare practices is expanding. But, other than manufacturer instructional manuals and some book chapters on CGMs, there are no standalone publications available with concise, non-commercial instructions on CGM prescription and use. Additionally, continuous glucose monitors are too often not used to their full and proper potential. This leaves users with suboptimal glucose control and can result in system abandonment. To address this, diabetes educator and author Gary Scheiner has created Practical CGM: Improving Patient Outcomes through Continuous Glucose Monitoring to give healthcare providers the skill to make more effective use of the data generated by continuous glucose monitors, in both real-time and on a retrospective analytic basis. Using a plain-language approach and distilling content to concise, practical tips and techniques, Scheiner has created a guide that will help practitioners optimize patient use of CGM systems and, ultimately, improve glucose control and patient health outcomes
Keywords: diabetes mellitus; Diabetes Mellitus; selfmonitoring glykemie; Blood Glucose Self-Monitoring; diabetologie